Interrogation system of signals from rotation sensors using tilted fiber Bragg gratings. Issue 1 (1st January 2020) - Ainur, Kozbakova; Kisała, Piotr; Waldemar, Wójcik; Aliya, Kalizhanova; Orken, Mamyrbayev; Maksat, Akhmetzhanov
Abstract: The paper herein is concerned with the system of interrogating the signals, entering from rotation sensors. The systems for analyzing the sensors thereof most often require capacity's reference measurement. It allows obtaining the measurement's higher resolution comparing to single-channel systems, in which it is impossible to measure the reference power. In case of single-channel solutions, there is most frequently tracked the wavelength shift, corresponding to the extreme, according to spectral specifications.